Pemanfaatan Ms.Excel untuk Pembukuan Keuangan UMKM Desa Bangsal Kecamatan Pampangan - Anita Desiani (Universitas Lancang Kuning, 2021)
Bangsal Village is in the Pampangan OKI of South Sumatera. Bangsal Village has community groups of micro small and medium enterprises (UMKM) including Buffalo Cattle, Palm Sugar and Buffalo Milk Jelly Producers. So far, the bookkeeping and financial reports carried out by the UMKM group are still manual paper records. In addition, UMKM don’t have staff to manage their financial reports, but by involving Ibnul Falah high school students. The students don’t have enough knowledge to use the computer technology like Ms.Excel for financial reports. The ms.excel workshop activities are given to community and ward village students in order to manage financial reports and bookkeepings easily. In addition, assistance and evaluation are also carried out so that the material is truly understood. The results are quite good, it can be seen from the average score obtained from the assignment, which is 76.7 and the average written test score is 78.1